Pengaruh Good Corporate Governance, Corporate Social Responsibility, dan Ukuran Perusahaan terhadap Manajemen Laba - Halim, Samuel Anthony; Gani, Petrus; Siregar, Hasrul; Fajrillah, Fajrillah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The purpose of this study was to analyze the effect of good corporate governance which is proxied with audit comitee, board of commissioners, and managerial ownership on earning management, analyze the effect of corporate social responsibility on earning management, analyze the effect of firm size on earning management, and analyze the effect of audit comitee, board of commissioners, managerial ownership, corporate social responsibility on earning management. The research method is hypothesis test. The data source of this research includes secondary data. Population in this study are BUMN companies listed on the Indonesia Stock Exchange for the 2016-2018 period which amounts to 20 companies. The sampling technique used in this study was purposive sampling and obtained a sample of 16 companies. The data analysis technique used is the classical assumption test which includes the normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, multiple linear regression, and hypothesis testing which includes the T test, F test, and the coefficient of determination test. The result obtained from the t result indicate that corporate social responsibility and audit comitee have a positive effect on earning management, while board of commissioners, managerial ownership, and firm size have a negative effect on earning management. From the result of the F test, the calculated of F value is obtained, 14,100 that is bigger than F table 2,32 which means that it shows that the independent variable simultaneously affects the dependent variable. The test coefficient of determination show that 58,2% earning management has effected by audit comitee, board of commissioners, managerial ownership, corporate social responsibility, and firm size. The remaining 41,8% has explained by other variable what is not explained in this study such as leverage and profitability.